FEM amd BEM computing costs for acoustical problems - BOLEJKO, R.; DOBRUCKI, A. (Archives of Acoustics, 2006)
FEM and BEM computing costs are compared for acoustical problems. The cost analysis was carried out for bounded areas of simple shapes for objects with acoustical losses (e.g. with sound absorbing materials). BEM’s variational-collocative scheme (DBEM) and its variational scheme (IBEM) were considered. Computing costs were calculated, taking into account main matrix composition costs and main system of equations solution costs. The costs were calculated for the type of adopted discrete elements and the order of quadrature used. Analytical relations for calculating main matrix composition costs for BEM have been derived. The analysis shows that FEM computing costs can be lower than BEM computing costs. Moreover, BEM computing costs are strongly dependent on the order of the quadrature used. The presented results provide a basis for the choice of the most cost-effective method depending on the size of an acoustical problem.